Energy Subsidies and Energy Consumption : A Cross-Country Analysis - Charap, Joshua (IMF Working Papers; Working Paper ;, 2013)
The economic and environmental implications of energy subsidies have received renewed attention from policymakers and economists in recent years. Nevertheless there remains significant uncertainty regarding the magnitude of the impact of energy subsidies on energy consumption. In this paper we analyze a panel of cross-country data to explore the responsiveness of energy consumption to changes in energy prices and the implications of our findings for the debate on energy subsidy reform. Our findings indicate a long-term price elasticity of energy demand between -0.3 and -0.5, which suggests that countries can reap significant long-term benefits from the reform of energy subsidies. Our findings also indicate that short-term gains from subsidy reform are likely to be much smaller, which suggests the need for either a gradual approach to subsidy reform or for more generous safety nets in the short term.